Assessing the Challenges of the Physical Learning Environment on Students’ Learning in Public Primary Schools in Dodoma - Issa, Fatna; Biswalo, Upendo (Journal of Education and Practice, 2025)
Purpose: A conducive physical learning environment is essential for promoting effective teaching, meaningful student engagement, and improved academic achievement. The purpose of this study was to assess the challenges of the physical learning environment and examine how these challenges affect students’ learning in selected public primary schools in Dodoma City. The study was guided by Environmental Psychology Theory. Methodology: The study employed a mixed-methods approach to provide a comprehensive understanding of the problem. Data were collected from pupils and teachers using questionnaires, focus group discussions, interviews, and observation. Findings: Findings show that a well-maintained physical learning environment plays a vital role in improving students’ learning outcomes. However, the study also identified several challenges, including shortage of classrooms, inadequate government funding, limited teaching and learning resources, and poor classroom conditions. Unique Contribution to Theory, Policy and Practice: The study advances Environmental Psychology Theory by showing how physical school conditions influence learners’ engagement, while offering practical guidance for improving teaching and classroom management. It also provides policymakers with evidence to strengthen infrastructure investment, maintenance, and resource allocation in public primary schools. The study recommends that the government invest in building more classrooms, ensuring regular maintenance of school infrastructure, and supplying adequate teaching and learning materials. Improving these aspects will create more conducive learning spaces and ultimately enhance student engagement and academic achievement in public primary schools in Dodoma.